Why Birthright Citizenship Matters for Immigrant Children: Impacts on Parental Educational Choice - Christina Felfe; Helmut Rainer; Judith Saurer (Center for Economic Studies and ifo Institute (CESifo), 2016)
Immigrant children often face educational disadvantages that stem from their parents' decision- making. For example, in many immigrant-receiving countries, immigrants are less likely than the native-born to enrol their children in preschool programs or enable them access to higher education. Thus, a key question is how to get immigrant parents to provide their children with similar educational opportunities as children in native families. This paper examines whether the introduction of birthright citizenship in Germany caused immigrant parents to adapt their educational choices for their offspring. We employ a difference-in-differences strategy which exploits a birth date cut-off determining whether a child became eligible for birthright citizenship or not. We find that the policy caused immigrant parents to (i) send their children to preschool more often; (ii) enrol their children earlier in primary school; and (iii) adjust their secondary school track choices in a way that enables their children better access to higher education.
Keywords: I21; J15; K37; 330